(untitled) (Research, Society and Development, 2023)
Introduction: One third of individuals living with major depressive disorder do not respond to antidepressant-based treatment. Suicidal ideation is a frequently present aggravating factor that is possibly lethal if not understood. The difficult control of the wide symptomatology related to depression in certain patients demonstrates the need for new and efficient therapeutic strategies. It was verified that ketamine presents antidepressant results when manipulated in subanesthetic doses. This research aims to verify the antidepressant potential of ketamine on major depressive disorder and resistant depressive disorder in scientific productions published between 2017 and 2022. Methodology: This is an integrative literature review. After searching the Virtual Health Library database, 100 publications were found, but only 12 articles met the inclusion criteria. Results and discussion: The NDMA receptor blockade promoted by ketamine is indicated as the cause of the rapid attenuation of depressive symptoms, which restores the synaptic dynamics of some maladjusted glutamatergic pathways in depressive disorders, restores the neural activity of important circuits related to stress, resilience and mood regulation, essentially modulating the emotional cognitive control function. In addition, it acts by regulating dysfunctional immunoinflammatory reactions involved in the pathophysiology of depression. Conclusion: The use of ketamine for the treatment of major depressive disorder and resistant depressive disorder has expressive and relevant results that make it a strong candidate to compose the arsenal adopted by international guidelines.